Safety Analysis for Pentavaccine Used in Premature Infants: Family Vaccination Centre’s Experiment - D. А. Novikova; L. S. Namazova-Baranova; А. G. Gayvoronskaya; М. I. Broeva; М. V. Fedoseenko (Вопросы современной педиатрии)
Combined vaccines containing non-cellular pertussis component and having low reactogenicity, increase vaccination coverage against controllable infections. However, the safety of vaccination in children dealing with health issues, as well as those having a history of premature infancy, requires additional research. The article presents reactogenicity analysis for the DTP-IPV/HIB pentavaccine during primary vaccination and revaccination of premature infants (n = 85), as well as vaccination of mature newborns (n = 1433) inoculated in accordance with the national Vaccination Calendar behind the schedule. The occurrence of post-vaccinal reactions in the premature infant group was the same as in the mature infant group and amounted to 41.2% and 45.0%; the occurrence of common reactions was 18.8% and 22.4%; local effects measured 25.8% and 27.9% respectively. Post-vaccinal reactions were either weak or moderate, not requiring treatment, and they would completely disappear by the end of the third post-vaccinal day. Simultaneous injection of pentavaccine and Hepatitis B vaccine and pneumococcal conjugate vaccine in children with a history of premature infancy, showed no influence during the post-vaccinal period. The reactogenicity of pentavaccine increased along with the vaccination ratio during the primary series of vaccinations.